The influence of mother tongue on university students’ English writing performance - a case study of Ningxia Medical University - Lu, Wei; Wan Zumusni Wan Mustapha,; Suryani Awang, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Due to the differences between English and Chinese, students often make errors in English writing. One of the reasons that students faced in writing is that their mother tongue language knowledge system is already established. Coupled with the constraints of the language environment, the students’ way of thinking and writing is prone to be influenced by their mother tongue. This paper highlights the current situation of the negative effects of the mother tongue on English writing among undergraduates in China, analyzes the main type of writing errors caused by their mother tongue, and provides targeted guidance to teaching them writing. The samples for the study are 57 learners of English as a second language (L2) students from Ningxia Medical University. They were asked to complete a writing task before their compositions were analyzed. Using Test Analysis Method, an analysis of writing compositions by this grade one university students found that the most common errors are caused by the negative effects of their mother tongue on English writing mainly on the use of articles, word order, and expressions of negation. Finally, to improve the quality of English teaching, this paper offers some suggestions on how to overcome the negative effects of the mother tongue on these students.